2015
DOI: 10.1042/bj20140935
|View full text |Cite
|
Sign up to set email alerts
|

Raptor ablation in skeletal muscle decreases Cav1.1 expression and affects the function of the excitation–contraction coupling supramolecular complex

Abstract: The protein mammalian target of rapamycin (mTOR) is a serine/threonine kinase regulating a number of biochemical pathways controlling cell growth. mTOR exists in two complexes termed mTORC1 and mTORC2. Regulatory associated protein of mTOR (raptor) is associated with mTORC1 and is essential for its function. Ablation of raptor in skeletal muscle results in several phenotypic changes including decreased life expectancy, increased glycogen deposits and alterations of the twitch kinetics of slow fibres. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…Consistently, in our study, total muscle force was not affected in mutant mice but we observed reduced specific strength of EDL muscle in HSA LR mice. Both specific and total muscle forces were increased upon AICAR, rapamycin, and AZD8055 treatments in young mutant mice, which may be mediated by mTORC1 inhibition as the signaling was shown to modulate Ca 2+ homeostasis and excitation-contraction coupling in skeletal muscle (66). Myotonia reduction and increase in muscle force were not caused by modified metabolic and contractile properties of the mutant muscle upon the applied short-term treatments.…”
Section: Discussionmentioning
confidence: 81%
“…Consistently, in our study, total muscle force was not affected in mutant mice but we observed reduced specific strength of EDL muscle in HSA LR mice. Both specific and total muscle forces were increased upon AICAR, rapamycin, and AZD8055 treatments in young mutant mice, which may be mediated by mTORC1 inhibition as the signaling was shown to modulate Ca 2+ homeostasis and excitation-contraction coupling in skeletal muscle (66). Myotonia reduction and increase in muscle force were not caused by modified metabolic and contractile properties of the mutant muscle upon the applied short-term treatments.…”
Section: Discussionmentioning
confidence: 81%
“…Rptor, a main accessory protein associated with mTOR in the mTORC1 complex, regulates mTOR signaling . In addition, Rptor depletion in mice muscle has been shown to inhibit mTORC1 activity and trigger a severe myopathy, characterized by structural and functional alterations compromising skeletal muscle excitation–contraction coupling . Hence, lowered levels of muscle Rptor in F mice could be sufficient to block activation of p70 S6K , reduce protein synthesis, and evoke dysfunctions of muscle dynamics during space flight.…”
Section: Resultsmentioning
confidence: 99%
“…Raptor null mice present with muscle atrophy, reduced oxidative capacity and increased glycogen stores that progressive results in a dystrophic phenotype (Bentzinger et al, 2008). A more recent study has linked these phenotypes to altered skeletal muscle excitation-contraction coupling, although the mechanisms underlying this pathology remain unknown (Lopez et al, 2015). Interestingly, neither whole body knockout of S6K1 or activation of 4E-BP1 in skeletal muscle, both of which phenocopy reduced mTORC1 signaling, display this severe phenotype (Selman et al, 2009; Tsai et al, 2015), suggesting that the Raptor knockout phenotype may derive from altered phosphorylation of both S6K1 and 4E-BP1, or possibly other mTORC1 targets.…”
Section: Mtor a Metabolic Master Regulatormentioning
confidence: 99%